The impact of a mainstream genetic testing pathway and socioeconomic factors on the uptake of germline genetic testing in breast cancer patients: results of the nationwide GENE-SMART study - Chiem Leonardo de Jong; Sabine Siesling; Ghita Carola Wilhelmina Maria Puts; Agnes Jager; Margreet Geertruda Elia Maria Ausems (Breast Cancer Research)
Summary Background Genetic testing in breast cancer patients is important for the patient’s local and systemic treatment choices and follow-up, as well as for their family members. Not all eligible patients currently undergo genetic testing and disparities persist in genetic testing uptake. It is unknown on the large scale whether pre-test counselling by non-genetic healthcare professionals (HCPs)–mainstream genetic testing (MGT) – improves overall genetic testing uptake and reduces disparities. We examined the impact of MGT on germline genetic testing uptake in general and in subgroups of socioeconomic status (SES) in particular. Methods In this retrospective nationwide cohort study, we selected all breast cancer patients from the Netherlands Cancer Registry who were eligible for genetic testing according to patient and tumour characteristics under the Dutch guidelines and who were diagnosed between 1-Jan-2017 and 31-Dec-2022. The primary outcome was genetic testing uptake. The influence of MGT and SES on overall uptake and uptake across different SES levels was evaluated using chi-squared tests and multivariable logistic regression analyses. Results A total of 12,071 breast cancer patients were included. Overall genetic testing uptake was 67%: 78% for MGT versus 63% in referral to a genetics department (RGD) (p < 0.001) with significantly higher odds of receiving genetic testing for MGT versus RGD (OR 2.48, 95% CI 2.14–2.87). Patients with low SES showed significantly lower odds of receiving genetic testing compared to those with a high SES (OR 0.71, 95% CI 0.61–0.83). In MGT, no significant difference was found between low and high SES in the likelihood of receiving genetic testing (OR 0.75, 95% CI 0.50–1.13). Conclusions MGT significantly increases genetic testing uptake among all eligible patients and across all SES subgroups, strongly encouraging further implementation of MGT. Educating HCPs about current disparities in genetic testing is essential to improve health equity in breast cancer care.